Changing the subject : how the women of Columbia shaped the way we think about sex and politics - Rosenberg, Rosalind, 1946- (Columbia University Press, 2004)
This remarkable story begins in the years following the Civil War, when reformers -- emboldened by the egalitarian rhetoric of the post--Civil War era -- pressed New York City's oldest institution of higher learning to admit women in the 1870s. Their effort failed, but within twenty years Barnard College was founded, creating a refuge for women scholars at Columbia, as well as an academic beachhead ""from which women would make incursions into the larger university."" By 1950, Columbia was granting more advanced degrees to women and hiring more female faculty than any other university.